Transparent bio-based nylon resin and preparation method thereof
By using a tubular reactor and nucleating agent during the preparation of nylon, combined with solid-phase tackification technology, the problem of nylon polymerization temperature control and stability is solved, the uniformity and service life of nylon resin are improved, and energy consumption is reduced and risk of blockage.
Patent Information
- Application Number
- CN202310792847.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
In the prior art, nylon polymerization needs to be carried out at high temperatures, which makes the reaction temperature difficult to accurately control, transparent nylon has poor stability and is prone to oxidation and yellowing, and polymers are prone to blocking the reaction equipment, and high energy consumption.
The nylon polycondensation is carried out using a tubular reactor, combining nucleating agents and solid-phase tackifying technology to accurately control the reaction temperature and molecular weight distribution, avoid oxidation and yellowing, and solid-phase tackifying is carried out in the extruder to reduce the risk of blockage.
The molecular weight uniformity and stability of nylon resin are improved, energy consumption is reduced, the service life of the resin is extended, and equipment blockage is avoided.
Smart Images

Figure BDA0004314084540000081 
Figure BDA0004314084540000091 
Figure BDA0004314084540000092
Abstract
Description
Technical Field
[0001] The invention relates to the field of nylon preparation, and in particular to a transparent bio-based nylon resin and a preparation method thereof. Background Art
[0002] The raw materials of nylon 6 and nylon 66 products currently used in large quantities in industry are mainly produced by reprocessing byproducts of petroleum refining. They are highly dependent on petroleum and there are environmental pollution problems during the preparation and processing. The synthesis of new green and sustainable nylon has also become a hot topic in recent years. Using cheap and renewable biomass resources as raw materials and using bioengineering methods to synthesize the raw materials required for nylon to prepare bio-based nylon products has become one of the future development trends of nylon.
[0003] Bio-based nylon materials refer to the raw materials needed to produce nylon (generally dibasic acids, diamines or cyclic lactams), which are obtained through bioengineering methods using renewable biomass resources such as glucose, cellulose, and vegetable oils (including castor oil, oleic acid and linoleic acid, etc.). Common bio-based nylon materials include nylon 56, nylon 510, nylon 5T, nylon 11, nylon 1010, nylon 610, nylon 410, nylon 1012, etc. Bio-based nylon has many applications in clothing fibers, natural gas pipelines, medical protective glasses, metal protective coatings, high-end fireproof oil and gas separators and crankshaft end covers, food packaging, automotive oil pipelines, LED packaging components, sports equipment, etc.
[0004] Transparent nylon is a part of special nylon. It is a thermoplastic nylon with microcrystalline or amorphous structure. Its light transmittance at a thickness of 2mm reaches more than 90%. It has better wear resistance, chemical resistance, flexibility and low density, and is significantly better than PC and PMMA in terms of environmental stress cracking resistance. At present, the annual consumption of transparent nylon is large, but the production capacity is very low. Traditional raw materials such as nylon 6 and nylon 66 are obtained by petroleum cracking. The raw material of synthetic transparent bio-based nylon such as nylon 5T is 1,5-pentanediamine, which can be converted from lysine through bioengineering, which can significantly reduce dependence on petroleum. PA5T has the advantages of high tensile strength and heat resistance, and can replace nylon 6 in the automotive industry and electrical and electronic industry. Nylon 5T has excellent welding resistance, excellent high temperature rigidity, excellent chemical resistance, low water absorption, excellent dimensional stability, excellent fluidity, and the characteristics of not easy to burr during molding. It can replace traditional nylon 6 and nylon 66 and will shine in the electronics and automotive industries. If 40% of nylon 66 is replaced by bio-based nylon in the future, its market size will reach 1.4 million tons / year, and the market prospects are broad. It is of great significance to carry out research and development of transparent bio-based nylon product preparation technology.
[0005] CN202211398042.6 discloses a bio-based copolymer transparent nylon and a preparation method thereof, the preparation method comprising: 1) mixing aliphatic diamine, aromatic diacid, isosorbide, aromatic acid, a catalyst and deionized water; 2) stirring and heating the reaction under a protective atmosphere, controlling the reaction temperature and reaction pressure, and the reaction time is 2 to 3 hours; 3) heating and pressurizing the reaction, controlling the reaction temperature and reaction pressure, and the reaction time is 3 to 4 hours; 4) unloading the pressure to a reaction pressure of 0.2 to 0.5 MPa, heating to a reaction temperature of 310 to 340°C, and then vacuuming the reaction time for 1 to 3 hours; and then pressurizing the material to obtain the bio-based copolymer transparent nylon.
[0006] CN202111351444.6 discloses a nylon comprising a bio-based nylon 5X polymer, wherein the raw materials of the bio-based nylon 5X polymer include nylon 5X salt, a phenolic antioxidant and a hindered amine light stabilizer. A method of polymerizing a concentrated polyamide 5X salt solution is adopted, and the polymerization process is divided into two steps, namely, pre-polymerization and post-polymerization, flash evaporation is performed between the two steps of polymerization, and finally the nylon 5X resin slices are processed at high temperature.
[0007] CN202211335848.0 discloses an application of low-melting-point copolymer nylon 56 / 66 in a transparent film. The transparency of the nylon 56 / 66 copolymer is improved by increasing the content of PA56 chain segments. The preparation method comprises the following steps: 1) directly mixing nylon 56 salt and nylon 56 salt crystals or their aqueous solutions in an inert atmosphere to obtain a nylon 56 / 66 salt solution; and 2) melt-polycondensing the nylon 56 / 66 salt solution to obtain copolymer nylon 56 / 66.
[0008] Although the above prior art provides a method for preparing transparent bio-based nylon, the following problems still exist: (1) Nylon polymerization needs to be carried out at high temperature, and the reaction temperature of the reactor polymerization cannot be accurately controlled, which will lead to uneven molecular weight distribution of the nylon product and generate more energy consumption; (2) Although the synthesized transparent bio-based nylon has high transparency, it has poor stability and is easily oxidized and yellowed after being left for a long time, which reduces its transparency and limits its application; (3) Solid-phase viscosity increase or vacuum extraction in the reaction equipment to increase the molecular weight is very likely to clog the reaction equipment, and the reaction process is unsafe and has high energy consumption. Summary of the invention
[0009] The purpose of the present invention is to provide a transparent bio-based nylon resin and a preparation method thereof, so as to solve the problems in the prior art that the polymerization temperature cannot be accurately controlled, the transparent nylon has poor stability and is easily oxidized and yellowed, and the polymer is easy to block the reaction equipment after the molecular weight increases.
[0010] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0011] In one aspect, the present invention provides a method for preparing a transparent bio-based nylon resin, the method comprising the following steps:
[0012] Bio-based pentamethylenediamine reacts with terephthalic acid and isophthalic acid to form a salt, thereby obtaining a mixed salt of nylon 5T and 5I;
[0013] The nylon 5T and 5I mixed salt is subjected to a prepolymerization reaction under the action of a catalyst to obtain a prepolymer of nylon 5T and 5I;
[0014] The obtained prepolymer and a nucleating agent are added into a tubular reactor for final polymerization to obtain a transparent nylon resin;
[0015] The obtained transparent nylon resin is pressurized and passed into an extruder, and a tackifier and a first compatibilizer are added for solid phase tackification, and then the strips are pulled and passed into a pelletizer for pelletizing, and after drying, transparent bio-based nylon resin chips are obtained.
[0016] In some embodiments of the present invention, the molar ratio of the bio-based pentamethylenediamine to terephthalic acid and isophthalic acid is 1:(1-1.2).
[0017] In some embodiments of the present invention, the molar ratio of terephthalic acid to isophthalic acid is 1:(2-4).
[0018] In some embodiments of the present invention, the salt-forming reaction is carried out in water, and the obtained nylon 5T, 5I mixed salt solution and a catalyst are added to a reactor to carry out the prepolymerization reaction to obtain nylon 5T, 5I prepolymers.
[0019] In some embodiments of the present invention, the reaction temperature of the salt-forming reaction is 60 to 90° C., and the reaction time is 0.5 to 2 h.
[0020] In some embodiments of the present invention, the mass ratio of the nylon 5T, 5I mixed salt to water is 1: (0.3-0.8),
[0021] In some embodiments of the present invention, the catalyst is a combination of anhydrous acetic acid and sodium hypochlorite in a molar ratio of 1:1.
[0022] In some embodiments of the present invention, the added amount of the catalyst is 0.3% to 2% of the mass of the nylon 5T and 5I mixed salt solution.
[0023] In some embodiments of the present invention, the reaction temperature of the prepolymerization reaction is 120-160° C., the reaction pressure is 1.5-4 MPa, and the reaction time is 0.5-2 h.
[0024] In some embodiments of the present invention, the nucleating agent, calculated based on a total weight of 100 parts, includes: 30-40 parts of nano-silicon dioxide, 15-30 parts of talc, 10-22 parts of kaolin, 5-10 parts of calcium hypochlorite, 5-10 parts of sodium hypochlorite, 1-5 parts of antioxidant, 0.5-3 parts of dispersant, and 1-3 parts of a second compatibilizer.
[0025] In some embodiments of the present invention, the antioxidant may be selected from phosphite antioxidants or sulfur-containing antioxidants, such as tris[2,4-di-tert-butylphenyl]phosphite.
[0026] In some embodiments of the present invention, the dispersant may be polyethylene low molecular weight wax or the like.
[0027] In some embodiments of the present invention, the second compatibilizer may be maleic anhydride grafted POE or the like.
[0028] In some embodiments of the present invention, the amount of the nucleating agent added is 5% to 30% of the mass of the nylon 5T and 5I mixed salt solution.
[0029] In some embodiments of the present invention, the specific surface area of the tubular reactor is greater than 80 m 2 / m 3 , with a pressure regulating device, the control range is 0 ~ 10MPa.
[0030] In some embodiments of the present invention, the reaction time of the final polymerization reaction is 1.5 to 3 hours, the reaction pressure is 1.5 to 4 MPa, and the reaction temperature is 220 to 260°C.
[0031] In some embodiments of the present invention, the tackifier may be BASF nylon polyester tackifier ADR4370.
[0032] In some embodiments of the present invention, the added amount of the tackifier is 0.2% to 2% of the mass of the transparent nylon resin.
[0033] In some embodiments of the present invention, the first compatibilizer may be POE grafted with maleic anhydride.
[0034] In some embodiments of the present invention, the added amount of the first compatibilizer is 0.5% to 2% of the mass of the transparent nylon resin.
[0035] In some embodiments of the present invention, during the solid phase viscosity increasing process, the temperature is 200-280° C., the time is 1-6 hours, and the extruder speed is 100-800 rpm.
[0036] Another aspect of the present invention provides a transparent bio-based nylon resin obtained by any of the above preparation methods.
[0037] In some embodiments of the present invention, the light transmittance of the transparent bio-based nylon resin is 90% to 95%.
[0038] In some embodiments of the present invention, the tensile strength of the transparent bio-based nylon resin is 80 to 100 GPa, preferably 82 to 87 GPa.
[0039] In some embodiments of the present invention, the number average molecular weight of the transparent bio-based nylon resin is 20,000 to 40,000, preferably 36,000 to 39,000.
[0040] The beneficial effects of the present invention include:
[0041] 1) The present invention introduces a tubular reactor into the nylon reaction in view of the characteristics of nylon dehydration polycondensation. Compared with a reactor, a tubular reactor can effectively remove the heat of reaction, accurately control the reaction temperature, achieve effective requirements for residence time, control the concentration distribution of reactants, and at the same time enable the nucleating agent and nylon prepolymer to be better cross-linked, and finally produce a nylon resin with uniform molecular weight; and further save energy consumption and improve the efficiency of the reaction. The present invention also adopts a reactor plus a tubular reactor, which can effectively control the reaction rhythm and make the reaction more complete.
[0042] 2) The present invention aims to solve the problem that nylon has too high viscosity and is easy to stick to the wall and clog the reactor. The process of solid phase viscosity increase of nylon is carried out after it is introduced into the extruder. Compared with the reactor, the extruder does not need to perform vacuum polycondensation, and the reaction conditions are milder and more controllable, which can make the molecular weight of nylon grow steadily, and then directly pull and extrude it without causing clogging problems.
[0043] 3) In view of the problem that transparent nylon resin materials are easily oxidized and yellowed by light during storage and transportation, thereby affecting the appearance and performance of nylon, the present invention designs a nucleating agent that can further improve the light transmittance of nylon resin, so that the transparent bio-based nylon resin will not be oxidized for a long time and will not yellow, thereby giving the resin a better service life. DETAILED DESCRIPTION
[0044] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0045] The invention provides a novel polymerization method for transparent bio-based nylon materials. By means of a reaction kettle plus a tubular reactor, the time, temperature and concentration distribution of reactants of the nylon polycondensation reaction are controlled, so that the molecular weight of the nylon can be evenly distributed, the performance is more stable, the reaction efficiency is improved, and the reaction energy consumption is reduced. At the same time, a novel nucleating agent is provided, which not only improves the transparency of the nylon resin, but also solves the problem that the nylon resin is easily oxidized and yellowed. The risk of blockage of the reaction equipment is reduced by means of solid phase viscosity enhancement in an extruder, thereby providing a more feasible method for efficiently producing transparent bio-based nylon resin.
[0046] The method for preparing the transparent bio-based nylon material provided by the present invention comprises the following steps:
[0047] S1, bio-based pentamethylenediamine reacts with terephthalic acid and isophthalic acid to form a salt to obtain a nylon 5T and 5I mixed salt;
[0048] S2, the nylon 5T, 5I mixed salt is prepolymerized under the action of a catalyst to obtain a nylon 5T, 5I prepolymer;
[0049] S3, adding the obtained prepolymer and the nucleating agent into a tubular reactor for final polymerization to obtain a transparent nylon resin;
[0050] S4, the obtained transparent nylon resin is pressurized and passed into an extruder, and a tackifier and a first compatibilizer are added for solid phase tackification, and then the strips are pulled and passed into a pelletizer for pelletizing, and after drying, transparent bio-based nylon resin chips are obtained.
[0051] The following is a detailed description of each step:
[0052] S1, bio-based pentamethylenediamine reacts with terephthalic acid and isophthalic acid to form a salt to obtain a nylon 5T and 5I mixed salt.
[0053] The molar ratio of the bio-based pentamethylenediamine to terephthalic acid and isophthalic acid is 1:(1-1.2). The ratio of terephthalic acid to isophthalic acid will affect the transparency of the obtained nylon material. Preferably, the molar ratio of terephthalic acid to isophthalic acid is 1:(2-4).
[0054] In some specific embodiments of the present invention, the salt-forming reaction is carried out in water, and the obtained nylon 5T and 5I mixed salt solution is directly used for the next reaction without treatment, and is added to the reactor with a catalyst to carry out the prepolymerization reaction to obtain nylon 5T and 5I prepolymers.
[0055] In some specific embodiments of the present invention, the reaction temperature of the salt-forming reaction is 60-90° C., and the reaction time is 0.5-2 h.
[0056] In some specific embodiments of the present invention, the mass ratio of the nylon 5T, 5I mixed salt to water is 1: (0.3-0.8),
[0057] S2. The nylon 5T and 5I mixed salt is subjected to a prepolymerization reaction under the action of a catalyst to obtain a prepolymer of nylon 5T and 5I.
[0058] The prepolymerization reaction is carried out in a reactor. Preferably, the reaction temperature of the prepolymerization reaction is 120-160° C., the reaction pressure is 1.5-4 MPa, and the reaction time is 0.5-2 h.
[0059] In some specific embodiments of the present invention, the catalyst is a combination of anhydrous acetic acid and sodium hypochlorite; the added amount of the catalyst is preferably 0.3% to 2% of the mass of the nylon 5T, 5I mixed salt solution.
[0060] S3, adding the obtained prepolymer and the nucleating agent into a tubular reactor for final polymerization to obtain a transparent nylon resin.
[0061] The final polymerization reaction is carried out in a tubular reactor. Preferably, the specific surface area of the tubular reactor is greater than 80 m 2 / m 3 , with a pressure regulating device, the control range is 0 ~ 10MPa.
[0062] Compared with the reactor, the tubular reactor can effectively remove the reaction heat, accurately control the reaction temperature, achieve the effective requirement for residence time, control the concentration distribution of the reactants, and make the nucleating agent and nylon prepolymer better cross-linked, and finally produce nylon resin with uniform molecular weight; and further save energy consumption and improve the efficiency of the reaction. The present invention adopts the method of reactor plus tubular reactor at the same time, which can effectively control the reaction rhythm and make the reaction more complete.
[0063] In some specific embodiments of the present invention, the nucleating agent, calculated based on 100 parts by total weight, includes: 30-40 parts of nano-silicon dioxide, 15-30 parts of talc, 10-22 parts of kaolin, 5-10 parts of calcium hypochlorite, 5-10 parts of sodium hypochlorite, 1-5 parts of antioxidant, 0.5-3 parts of dispersant, and 1-3 parts of second compatibilizer.
[0064] Nano silicon dioxide, talcum powder and kaolin are the main components of the nucleating agent, calcium hypochlorite and sodium hypochlorite have both catalytic and anti-yellowing effects, and the components and proportions of the nucleating agent developed by the present invention can obtain the best transparency and anti-yellowing effect.
[0065] In some specific embodiments of the present invention, the antioxidant is a phosphite antioxidant or a sulfur-containing antioxidant, such as tri[2,4-di-tert-butylphenyl]phosphite, dibutyl pyrophosphate; the dispersant is polyethylene low molecular weight wax; and the second compatibilizer is maleic anhydride grafted POE.
[0066] In some specific embodiments of the present invention, the amount of the nucleating agent added is 5% to 30% of the mass of the nylon 5T and 5I mixed salt solution.
[0067] In some specific embodiments of the present invention, the reaction time of the final polymerization reaction is 1.5 to 3 hours, the reaction pressure is 1.5 to 4 MPa, and the reaction temperature is 220 to 260°C.
[0068] S4, the obtained transparent nylon resin is pressurized and passed into an extruder, and a tackifier and a first compatibilizer are added for solid phase tackification, and then the strips are pulled and passed into a pelletizer for pelletizing, and after drying, transparent bio-based nylon resin chips are obtained.
[0069] The present invention conducts the solid phase viscosity enhancement process of nylon after it is introduced into the extruder. Compared with the reactor, the extruder does not need to perform vacuum polycondensation, and the reaction conditions are milder and more controllable, so that the molecular weight of nylon can be stably increased, and then it can be directly pulled and extruded without causing blockage problems.
[0070] The tackifier may be a conventional tackifier in the art, such as BASF nylon polyester tackifier ADR4370 used in some specific embodiments of the present invention. The added amount of the tackifier is preferably 0.2% to 2% of the mass of the transparent nylon resin.
[0071] In some specific embodiments of the present invention, the first compatibilizer is maleic anhydride grafted POE. The addition amount of the first compatibilizer is preferably 0.5% to 2% of the mass of the transparent nylon resin.
[0072] In some specific embodiments of the present invention, during the solid phase viscosity increasing process, the temperature is 200-280° C., the time is 1-6 hours, and the speed of the extruder is 100-800 rpm.
[0073] The transparent bio-based nylon resin obtained by any of the above preparation methods preferably has a light transmittance of 90% to 95%; a tensile strength of 80 to 100 GPa, more preferably 82 to 87 GPa; and a number average molecular weight of 20,000 to 40,000, more preferably 36,000 to 39,000.
[0074] Some specific examples are provided below for illustration, wherein all numerical values specified (such as temperature, time, concentration and weight, etc., including the range of each thereof) are generally approximate values that can be appropriately changed (+) or (-) in increments of 0.1 or 1.0. All numerical values specified can be understood as being preceded by the term "about".
[0075] The formula of the nucleating agent used in the following examples and comparative examples is: 40 parts of nano-silicon dioxide, 20 parts of talc, 15 parts of kaolin, 10 parts of calcium hypochlorite, 10 parts of sodium hypochlorite, 2 parts of antioxidant, 2 parts of dispersant, and 1 part of the second compatibilizer. Among them, the antioxidant is tris [2,4-di-tert-butylphenyl] phosphite; the dispersant is polyethylene low molecular weight wax; and the second compatibilizer is maleic anhydride grafted POE.
[0076] The tackifier is BASF nylon polyester tackifier ADR4370; the first compatibilizer is maleic anhydride grafted POE.
[0077] Example 1
[0078] The following examples are all carried out on the basis of this experimental procedure, including:
[0079] S1. Take 16.62g of terephthalic acid and 66.45g of isophthalic acid and put them into 41.2g of pure water. After heating to 80°C, stir. After the terephthalic acid and isophthalic acid are dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 80°C for 1h. After the solution becomes transparent, stop the reaction. At this time, the pH value of the obtained nylon 5T and 5I salt solution is measured to be 6.8.
[0080] S2. Take 100g of the prepared nylon 5T and 5I salt solution and put it into a reaction kettle, add 0.5g of anhydrous acetic acid and 0.5g of sodium hypochlorite dropwise. Pass nitrogen three times until there is no air in the kettle. Under nitrogen protection, carry out prepolymerization at 140°C. After reacting for 1h, obtain nylon 5T and 5I prepolymers.
[0081] S3. The prepolymers of nylon 5T and 5I are introduced into a tubular reactor, and 30 g of a nucleating agent is added. After the tubular reactor is sealed, the temperature is raised to 240° C. and the reaction is carried out for 3 hours to obtain nylon 5T and 5I molten resins.
[0082] S4. Continue to pressurize the obtained nylon 5T and 5I molten resins (just give a little pressure to make it enter the extruder smoothly) and pass them into the extruder, and add 2.8g of tackifier and 2g of compatibilizer, and carry out solid phase viscosity enhancement in the extruder. During the solid phase viscosity enhancement, the extruder temperature is 240°C and the extruder speed is 500rpm. React in the extruder for 5h, then pull the strands and pass them into the pelletizer for pelletizing. After drying, transparent bio-based nylon resin chips are obtained.
[0083] Table 1 shows the quality of the nylon product, its number average molecular weight and tensile strength obtained by changing the molar ratio of isophthalic acid, terephthalic acid and pentamethylenediamine according to the above experimental conditions.
[0084] Table 1
[0085]
[0086] It can be seen from the data in Table 1 that when the ratio of diamine to diacid is 1:(1-1.2), the molecular weight of the obtained nylon resin ranges from 38000 to 39000, and the tensile strength ranges from 82 to 86 GPa.
[0087] Example 2
[0088] Example 2 is similar to Example 1-2, the only difference being that in the salt-forming reaction, the mass of the pure water added is different. In Example 2, the amount of pure water added is changed, resulting in different mass ratios of 5T and 5I salts to pure water. The data on the mass of the nylon product obtained, its number average molecular weight, and tensile strength are shown in Table 2.
[0089] Table 2
[0090]
[0091] From the data in Table 2, it can be seen that when the mass ratio of nylon 5T, 5I salt to pure water is 1:(0.3-0.8), the molecular weight range of the obtained nylon resin is 36000-39000, and the tensile strength is between 83-86 GPa.
[0092] Example 3
[0093] Example 3 is similar to Example 2-2, except that the mass of the catalyst anhydrous acetic acid and sodium hypochlorite added in the reactor is different. In Example 3, the addition amount of anhydrous ethanol and sodium hypochlorite is changed, and the data of the mass of the nylon product obtained, its number average molecular weight and tensile strength are shown in Table 3.
[0094] Table 3
[0095]
[0096] From the data in Table 3, it can be seen that when the ratio of anhydrous acetic acid and sodium hypochlorite added to the nylon 56 salt solution is 0.3% to 2%, the molecular weight of the obtained nylon resin ranges from 38,000 to 39,000, and the tensile strength is between 84 and 86 GPa.
[0097] Example 4
[0098] Example 4 is similar to Example 3-3, the only difference being that the reaction temperature for the prepolymerization reaction in the reactor is different. In Example 4, the reaction temperature of the prepolymerization reaction in the reactor is changed, the pressure in the reactor, and the quality of the nylon product finally obtained and its number average molecular weight and tensile strength are shown in Table 4.
[0099] Table 4
[0100]
[0101] From the data in Table 4, it can be seen that when the prepolymerization temperature in the reactor is 120-140°C, the molecular weight of the obtained nylon resin ranges from 38,000 to 39,000, and the tensile strength is between 84 and 86 GPa.
[0102] Example 5
[0103] Example 5 is similar to Example 4-2, the only difference being that the reaction time for the prepolymerization reaction in the reactor is different. In Example 5, the reaction time for the prepolymerization reaction in the reactor is changed, and the data on the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 5.
[0104] Table 5
[0105]
[0106] It can be seen from the data in Table 5 that when the prepolymerization time in the reactor is 0.5 to 2 hours, the molecular weight of the obtained nylon resin ranges from 37,000 to 39,000, and the tensile strength is between 83 and 87 GPa.
[0107] Example 6
[0108] Example 6 is similar to Example 5-3, the only difference being the mass of the nucleating agent added in the reaction tube. In Example 6, the mass of the nucleating agent added in the reaction tube was changed, and the data of the mass of the nylon product, its number average molecular weight, tensile strength and resin transparency obtained are shown in Table 6.
[0109] Table 6
[0110]
[0111] From the data in Table 6, it can be seen that when the amount of nucleating agent added accounts for 5% to 30% of the mass of the nylon salt solution, the molecular weight of the obtained nylon resin ranges from 37000 to 39000, and the tensile strength is between 83 and 87 GPa.
[0112] Example 7
[0113] Example 7 is similar to Example 6-4, the only difference is that the reaction temperature of the final polymerization reaction in the reaction tube is different. In Example 7, the reaction temperature of the final polymerization reaction in the reaction tube is changed, the pressure in the reaction tube, and the quality of the nylon product finally obtained, its number average molecular weight and tensile strength are shown in Table 7.
[0114] Table 7
[0115]
[0116] It can be seen from the data in Table 7 that when the reaction temperature of the final polymerization reaction in the tubular reactor is 220-240°C, the molecular weight range of the obtained nylon resin is 38000-39000, and the tensile strength is between 84-86 GPa.
[0117] Example 8
[0118] Example 8 is similar to Example 7-2, the only difference being that the reaction time for the final polymerization reaction in the reaction tube is different. In Example 8, the reaction time for the final polymerization reaction in the reaction tube is changed, and the data on the quality of the nylon product obtained, its number average molecular weight, and tensile strength are shown in Table 8.
[0119] Table 8
[0120]
[0121] It can be seen from the data in Table 8 that when the reaction time of the final polymerization reaction in the tubular reactor is 1.5 to 3 hours, the molecular weight of the obtained nylon resin ranges from 37,000 to 39,000, and the tensile strength is between 84 and 86 GPa.
[0122] Example 9
[0123] Example 9 is similar to Example 8-3, the only difference being that when solid phase viscosity increasing is performed in the extruder, the mass of the added viscosity increasing agent or the first compatibilizer is different. In Example 9, the added mass of the viscosity increasing agent or the first compatibilizer is changed, and the data of the mass of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Tables 9 and 10.
[0124] Table 9
[0125]
[0126] Table 10
[0127]
[0128] It can be seen from the data in Table 9 that when the ratio of the tackifier added to the nylon 56 resin is 0.2% to 2%, the molecular weight of the obtained nylon resin ranges from 36,000 to 39,000, and the tensile strength is between 84 and 87 GPa.
[0129] It can be seen from the data in Table 10 that when the addition amount of the first compatibilizer is 0.5% to 2%, the molecular weight of the obtained nylon resin ranges from 37000 to 38000, and the tensile strength is between 85 and 86 GPa.
[0130] Example 10
[0131] Example 10 is similar to Example 9-3, the only difference being that the reaction temperature is different when solid phase viscosity enhancement is performed in the extruder. In Example 10, the reaction temperature of the extruder is changed, and the data of the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 11.
[0132] Table 11
[0133]
[0134] It can be seen from the data in Table 11 that when the solid phase viscosity increasing reaction temperature is 220-240°C, the molecular weight of the nylon resin is in the range of 38000-39000, and the tensile strength is in the range of 84-86 GPa.
[0135] Embodiment 11
[0136] Example 11 is similar to Example 10-2, the only difference being that the reaction time for solid phase viscosity enhancement in the extruder is different. In Example 11, the reaction time for solid phase viscosity enhancement in the extruder is changed, and the data on the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 12.
[0137] Table 12
[0138]
[0139] It can be seen from the data in Table 12 that when the solid phase viscosity increasing reaction time is 1 to 5 hours, the molecular weight of the nylon resin is in the range of 36000 to 39000, and the tensile strength is in the range of 83 to 86 GPa.
[0140] Comparative Example 1
[0141] In this comparative example, the final polymerization reaction was carried out in a reactor.
[0142] S1. Take 16.62g of terephthalic acid and 66.45g of isophthalic acid and put them into 41.2g of pure water. After heating to 80°C, stir. After the terephthalic acid and isophthalic acid are dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 80°C for 1h. When the solution becomes clear, stop the reaction. At this time, the pH value of the obtained nylon 5T and 5I salt solution is measured to be 6.8.
[0143] S2. Take 100g of the above-prepared nylon 5T, 5I salt solution and 30g of nucleating agent and put them into the reactor, and add 0.5g of anhydrous acetic acid and 0.5g of sodium hypochlorite. Pass nitrogen three times until there is no air in the reactor. Under nitrogen protection, prepolymerization reaction is carried out at 140°C. After 1h, the temperature is raised to 220°C, and the final polymerization reaction is continued for 3h to obtain a transparent bio-based nylon molten resin.
[0144] S3. Continue to introduce the transparent bio-based nylon molten resin into the extruder, add 2.8 g of a tackifier and 2 g of a compatibilizer, and perform solid phase thickening in the extruder. During the solid phase thickening, the extruder temperature is 240° C., the extruder speed is 500 rpm, and the reaction is carried out in the extruder for 5 hours. Subsequently, the strips are pulled and introduced into a pelletizer for pelletizing, and transparent bio-based nylon resin chips are obtained after drying.
[0145] In this comparative example, all the above conditions were the same, and only the final polymerization step was changed. The mass of the obtained nylon 56 resin was 135.12 g, the number average molecular weight of nylon was 35500, and the tensile strength was 82.63 GPa.
[0146] It can be seen from the comparison between this comparative example and Example 1 that, under the condition that other conditions are the same but the final polymerization reaction in the reaction tube is omitted, the yield of the final nylon product, as well as the number average molecular weight and tensile strength are reduced.
[0147] Comparative Example 2
[0148] In this comparative example, solid phase viscosity enhancement was carried out in a tubular reactor.
[0149] S1. Take 16.62g of terephthalic acid and 66.45g of isophthalic acid and put them into 41.2g of pure water. After heating to 80°C, stir. After the terephthalic acid and isophthalic acid are dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 80°C for 1h. After the solution becomes clear, stop the reaction. At this time, the pH value of the obtained nylon 5T and 5I salt solution is measured to be 6.8.
[0150] S2. Take 100g of the above-prepared nylon 5T, 5I salt solution and put it into a reaction kettle, add 0.5g of anhydrous acetic acid and 0.5g of sodium hypochlorite dropwise. Pass nitrogen three times until there is no air in the kettle. Under nitrogen protection, carry out prepolymerization at 140°C. After reacting for 1h, obtain nylon 5T, 5I prepolymers.
[0151] S3. The prepolymers of nylon 5T and 5I are introduced into a tubular reactor, and 30 g of a nucleating agent, 2.8 g of a tackifier and 2 g of a compatibilizer are added. After the tubular reactor is sealed, the temperature is raised to 220°C, and after reacting for 3 hours, the air is vented to normal pressure, and then vacuumed to 0.2-0.8 MPa. After 30 minutes, nylon 5T and 5I molten resins are obtained.
[0152] S4, continue to feed the nylon 5T and 5I molten resins into the extruder at an extruder temperature of 240°C and an extruder speed of 500 rpm for 5 hours, then pull the strands and feed them into a pelletizer for pelletizing, and obtain transparent bio-based nylon resin chips after drying.
[0153] In this comparative example, all the above conditions were the same, except that the solid phase viscosity enhancement step was changed by advancing it to the S3 final polymerization step. The mass of the obtained nylon resin was 136.12 g, the number average molecular weight of nylon was 35,500, and the tensile strength was 83.73 GPa.
[0154] It can be seen from the comparison between this comparative example and Example 1 that other conditions are the same, except that the step of solid phase viscosity enhancement in the extruder in the present application is advanced to the final polymerization step, the yield of the final nylon product, as well as the number average molecular weight and tensile strength are reduced.
[0155] Comparative Example 3
[0156] No nucleating agent was added in this comparative example.
[0157] S1. Take 16.62g of terephthalic acid and 66.45g of isophthalic acid and put them into 67.08g of pure water. Heat it to 80°C and stir it. After the terephthalic acid and isophthalic acid are dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 80°C for 1h. Stop the reaction after the solution becomes transparent. At this time, the pH value of the obtained nylon 5T and 5I salt solution is measured to be 6.8.
[0158] S2. Take 100g of the prepared nylon 5T and 5I salt solution and put it into a reaction kettle, add 1g of anhydrous acetic acid and 1g of sodium hypochlorite dropwise. Pass nitrogen three times until there is no air in the kettle. Under nitrogen protection, carry out prepolymerization at 140°C. After reacting for 2h, obtain nylon 5T and 5I prepolymers.
[0159] S3. The prepolymers of nylon 5T and 5I are introduced into a tubular reactor. After the tubular reactor is sealed, the temperature is raised to 220° C. and the reaction is carried out for 3 hours to obtain nylon 5T and 5I molten resins.
[0160] S4. Continue to introduce nylon 5T and 5I molten resins into the extruder, add 2.8 g of tackifier and 2 g of compatibilizer, and perform solid phase viscosity enhancement in the extruder. During the solid phase viscosity enhancement, the extruder temperature is 240°C and the extruder speed is 500 rpm. After reacting in the extruder for 5 hours, the strips are subsequently pulled and introduced into a pelletizer for pelletizing. After drying, transparent bio-based nylon resin chips are obtained.
[0161] In this comparative example, under the same conditions as above, only the nucleating agent was not added, and the mass of the obtained nylon resin was 137.12g, the number average molecular weight of nylon was 37000, the tensile strength was 84.63GPa, the resin transparency was only 75%, and the resin turned yellow after being placed under ultraviolet light and room temperature for 24 hours, and the yellowing value ΔE was 26.4. However, the nylon resin added with the nucleating agent in the embodiment of the present invention did not turn yellow after being placed under ultraviolet light and room temperature for 24 hours, and the yellowing value ΔE was 12.2.
[0162] By comparing this comparative example with Example 6, it can be seen that other conditions are the same, except that no nucleating agent is added, the transmittance of the nylon product finally obtained is greatly reduced, and yellowing is obvious.
[0163] Example 12
[0164] Example 12 is similar to Example 6-4, except that the ratio of the nucleating agent added in the reaction tube is different. In Example 12, the nucleating agent added in the reaction tube is changed, and the data of the quality of the nylon product, its number average molecular weight, tensile strength, resin transparency, and yellowing value are shown in Table 13, Table 14, and Table 15. Except for the change in the ratio of the components listed in the table, the ratios of other components remain unchanged and are increased or decreased in equal proportions.
[0165] Table 13
[0166]
[0167] From the data in Table 13, it can be seen that nano-silicon dioxide can improve the transparency of nylon resin. When the addition amount is 30% to 40%, the transparency is 92% to 94%.
[0168] Table 14
[0169]
[0170] In Table 14, the ratio between talc and kaolin remains unchanged. From the data in Table 13, it can be seen that talc and kaolin can improve the transparency of nylon resin. When the addition amount is 30% to 40%, the transparency is 93% to 94%.
[0171] Table 15
[0172]
[0173] In Table 15, the ratio between calcium hypochlorite and sodium hypochlorite remains unchanged. From the data in Table 14, it can be seen that calcium hypochlorite and sodium hypochlorite can further enhance the anti-yellowing ability of nylon resin. When the addition amount is 10% to 20%, the yellowing value is between 12 and 19.
[0174] The tensile strength involved in the above embodiments and comparative examples was measured by a universal tensile machine, the number average molecular weight was measured by GPC gel chromatography, the transparency was tested according to "GB 2410-1980 Transparent Plastics Transmittance Test Method", and the yellowing was tested according to "GB / T 7921-2008".
[0175] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a transparent bio-based nylon resin, wherein: The preparation method comprises the following steps: Bio-based pentamethylenediamine reacts with terephthalic acid and isophthalic acid to form a salt, thereby obtaining a mixed salt of nylon 5T and 5I; The nylon 5T and 5I mixed salt is subjected to a prepolymerization reaction under the action of a catalyst to obtain a prepolymer of nylon 5T and 5I; The obtained prepolymer and a nucleating agent are added into a tubular reactor for final polymerization to obtain a transparent nylon resin; The obtained transparent nylon resin is pressurized and passed into an extruder, and a tackifier and a first compatibilizer are added for solid phase tackification, and then the strips are pulled and passed into a pelletizer for pelletizing, and after drying, transparent bio-based nylon resin chips are obtained.
2. The preparation method according to claim 1, wherein The nucleating agent, calculated based on 100 parts by total weight, includes: 30-40 parts of nano silicon dioxide, 15-30 parts of talc, 10-22 parts of kaolin, 5-10 parts of calcium hypochlorite, 5-10 parts of sodium hypochlorite, 1-5 parts of antioxidant, 0.5-3 parts of dispersant, and 1-3 parts of second compatibilizer.
3. The preparation method according to claim 1, wherein The added amount of the nucleating agent is 5% to 30% of the mass of the nylon 5T and 5I mixed salt solution.
4. The preparation method according to claim 2, wherein The antioxidant is selected from phosphite antioxidants or sulfur-containing antioxidants.
5. The preparation method according to claim 2, wherein: The dispersant is polyethylene low molecular wax.
6. The preparation method according to claim 1 or 2, wherein: The first compatibilizer and the second compatibilizer are both maleic anhydride grafted POE.
7. The preparation method according to claim 2, wherein: The molar ratio of the bio-based pentamethylenediamine to terephthalic acid and isophthalic acid is 1:(1-1.2).
8. The preparation method according to claim 1, wherein The molar ratio of terephthalic acid to isophthalic acid is 1:(2-4).
9. The preparation method according to claim 1, wherein The salt-forming reaction is carried out in water, and the obtained nylon 5T and 5I mixed salt solution and a catalyst are added into a reactor to carry out the prepolymerization reaction to obtain nylon 5T and 5I prepolymers.
10. The preparation method according to claim 9, wherein: The reaction temperature of the salt-forming reaction is 60-90° C., and the reaction time is 0.5-2 h.
11. The preparation method according to claim 9, wherein: The mass ratio of the nylon 5T, 5I mixed salt to water is 1:(0.3-0.8).
12. The preparation method according to claim 9, wherein: The catalyst is a combination of anhydrous acetic acid and sodium hypochlorite in a molar ratio of 1:
1.
13. The preparation method according to claim 12, wherein: The added amount of the catalyst is 0.3% to 2% of the mass of the nylon 5T and 5I mixed salt solution.
14. The preparation method according to claim 1, wherein: The reaction temperature of the prepolymerization reaction is 120-160° C., and the reaction time is 0.5-2 h.
15. The preparation method according to claim 1, wherein: The specific surface area of the tubular reactor is greater than 80m 2 / m 3 , with a pressure regulating device, the control range is 0 ~ 10MPa.
16. The preparation method according to claim 1, wherein: The reaction time of the final polymerization reaction is 1.5 to 3 hours, and the reaction temperature is 220 to 260°C.
17. The preparation method according to claim 1, wherein: The added amount of the tackifier is 0.2% to 2% of the mass of the transparent nylon resin.
18. The preparation method according to claim 1, wherein: The added amount of the first compatibilizer is 0.5% to 2% of the mass of the transparent nylon resin.
19. The preparation method according to claim 1, wherein: During the solid phase viscosity enhancement process, the temperature is 200-280° C. and the time is 1-6 hours.
20. A transparent bio-based nylon resin obtained by the preparation method according to any one of claims 1 to 19.
21. The transparent bio-based nylon resin according to claim 20, wherein: The transparent bio-based nylon resin has a light transmittance of 90% to 95%, a tensile strength of 80 to 100 GPa, and a number average molecular weight of 20,000 to 40,000.
Citation Information
Patent Citations
Nylon and preparation method thereof
CN103102486A
Method for continuously preparing polyamide with low gel content and narrow molecular weight distribution and product thereof
CN114106319A
Continuous melt polymerization method for high-temperature-resistant nylon
CN114316255A
Production of nylon resin and production of nylon resin composition
JP2000256461A
Cited By
Preparation method of high-viscosity polyamide resin
CN120829578A